2010
DOI: 10.1055/s-0030-1249861
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cytotoxic Activity ofSchisandra chinensisLignans

Abstract: Using exhaustive chromatographic separation we have isolated (-)-tigloyl-deangeloyl-gomisin F as a novel dibenzocyclooctadiene lignan from schisandra chinensis. With the help of HPLC, we further isolated (+)-schisandrin, (+)-deoxyschisandrin, (+)-γ-schisandrin, (-)-gomisin J, (+)-gomisin A, (-)-gomisin N, (-)-tigloyl-gomisin P, (-)-wuweizisu C, (-)-gomisin D, rubrisandrin A, (-)-gomisin G, (+)-gomisin K (3) and (-)-schisantherin C. A full NMR description of (-)-schisantherin C was carried out with the aim to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…Previously, tigloylgomisin P (2) had been reported to possess cytotoxicity against the Nicotiana BY-2 cell line (Smejkal et al, 2010) and schisanlactone B (8) was found to inhibit human cancer cell lines Bel-7402 and HL-60 (Wang et al, 2006). No prior literature had addressed the cytotoxicities of cagayanone (3), (À)-gomisin L 2 (4), micranoic acid B (5) and lancifodilactone H (6).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, tigloylgomisin P (2) had been reported to possess cytotoxicity against the Nicotiana BY-2 cell line (Smejkal et al, 2010) and schisanlactone B (8) was found to inhibit human cancer cell lines Bel-7402 and HL-60 (Wang et al, 2006). No prior literature had addressed the cytotoxicities of cagayanone (3), (À)-gomisin L 2 (4), micranoic acid B (5) and lancifodilactone H (6).…”
Section: Resultsmentioning
confidence: 99%
“…Recently a group from Johns Hopkins isolated lignans from Schisandra chinensis and demonstrated its anti-proliferative activity in human colorectal carcinoma (Gnabre et al, 2010) and cytotoxicity against colon cancer cell line LoVo (Smejkal et al, 2010). Their effects were reported on structure-activity relationships (Gnabre et al, 2010).…”
Section: Anti-cancermentioning
confidence: 99%
“…G.A has multiple biological activities including memory improving and hepatoprotective, antihypertensive, antidiabetic, and anti-inflammatory effects (Kim et al, 2006; Kwon et al, 2011; Park et al, 2012; Wang et al, 2014; Jiang et al, 2015). G.A also inhibits hepatocarcinogenesis and shows cytotoxicity against human CRC cell lines (LoVo, HCT116) and A2780 human ovarian cancer cells (Ohtaki et al, 1996; Smejkal et al, 2010; Hwang et al, 2011; Jeong et al, 2017). However, the effects of G.A on the metastatic phenotype and metastasis of CRC cells have not been elucidated using in vivo models.…”
Section: Introductionmentioning
confidence: 99%